The relative a priori. Towards a pragmatist conception of science? - Mariano SANJUÁN SALINA (Artefactos, 2019)
I put forward a revision of the concept of the relative a priori from Michael Friedman’s proposal. I will begin by exposing those aspects of Carnap and Kuhn that underlie the static and dynamic dimensions of Friedman’s project. It will be argued that, despite its virtues, the lack of pragmatic awareness prevents him from properly characterize theory choice. Hereafter, some criticism will be presented. Lastly, stemming from criticism, some pragmatic readings of the relative a priori will be explored as overcoming the issues addressed.